2020
DOI: 10.3389/fphys.2020.611550
|View full text |Cite
|
Sign up to set email alerts
|

Network Physiology of Exercise: Vision and Perspectives

Abstract: The basic theoretical assumptions of Exercise Physiology and its research directions, strongly influenced by reductionism, may hamper the full potential of basic science investigations, and various practical applications to sports performance and exercise as medicine. The aim of this perspective and programmatic article is to: (i) revise the current paradigm of Exercise Physiology and related research on the basis of principles and empirical findings in the new emerging field of Network Physiology and Complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 168 publications
3
90
0
Order By: Relevance
“…Conceptually, network physiology is the “microscopic” as well as “dynamic” extension of the “macroscopic” perspective of Rothman's model of sufficient causes. Rather than simply describing the phenomenological characteristics associated with health and disease, network physiology aims to elucidate the spatio-temporal system integration and the dynamics between the organ, cell, metabolomic and genomic layers of biological systems ( Figure 7 ) ( 39 ). Each layer has its own distinctive dynamics which influences the dynamic interactions across layers.…”
Section: Health Patterns—the Outcome Of Complex-adaptive Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptually, network physiology is the “microscopic” as well as “dynamic” extension of the “macroscopic” perspective of Rothman's model of sufficient causes. Rather than simply describing the phenomenological characteristics associated with health and disease, network physiology aims to elucidate the spatio-temporal system integration and the dynamics between the organ, cell, metabolomic and genomic layers of biological systems ( Figure 7 ) ( 39 ). Each layer has its own distinctive dynamics which influences the dynamic interactions across layers.…”
Section: Health Patterns—the Outcome Of Complex-adaptive Dynamicsmentioning
confidence: 99%
“…Each layer has its own distinctive dynamics which influences the dynamic interactions across layers. Alteration in the interactions within a layer will not only change the dynamics of that layer but also those of interacting layers, and thereby shift the integrated function of the system-as-a-whole ( 39 , 40 ). Physiological network properties have pragmatic clinical implications as exemplified in patients with liver failure ( 41 ) or severe critical illness ( 42 )—the breakdown/loss of network interconnection between the layers of system organization is associated with poor outcomes.…”
Section: Health Patterns—the Outcome Of Complex-adaptive Dynamicsmentioning
confidence: 99%
“…Nevertheless, the immobility associated with keeping the same posture during long periods can induce, more than avoiding, health problems. Movement is necessary to coordinate organs [12], activate psychobiological functions and stimulate the body and the mind to keep the psycho-emotional and physical states that ensure job satisfaction, productivity, work-life balance, wellbeing and health.…”
Section: New Perspectives and Practical Recommendationsmentioning
confidence: 99%
“…Scientific evidence has shown that regular exercise does improve not only the physical but also the psycho-emotional status, contributing to reduce negative emotion, relieve fatigue, improve sleep quality, and prevent cardiovascular and cerebrovascular diseases, among others [12]. Most of the studies testing the benefits of exercise on healthy people and clinical patients apply exercise protocols and standardized programs based on WHO and ACSM guidelines [3,13] and training recommendations [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation